Do China and oil exporters influence major currency configurations? - Marcel Fratzscher; Arnaud Mehl (European Central Bank (ECB), 2008)
This paper analyses the impact of the shift away from a US dollar focus of systemically important emerging market economies (EMEs) on configurations between the US dollar, the euro and the yen. Given the difficulty that fixed or managed US dollar exchange rate regimes remain pervasive and reserve compositions mostly kept secret, the identification strategy of the paper is to analyse the market impact on major currency pairs of official statements made by EME policy-makers about their exchange rate regime and reserve composition. Developing a novel database for 18 EMEs, we find that such statements not only have a statistically but also an economically significant impact on the euro, and to a lesser extent the yen against the US dollar. The findings suggest that communication hinting at a weakening of EMEs' US dollar focus contributed substantially to the appreciation of the euro against the US dollar in recent years. Interestingly, EME policy-makers appear to have become more cautious in their communication more recently. Overall, the results underscore the growing systemic importance of EMEs for global exchange rate configurations.
Keywords: E58; F30; F31; F36; G15; 330; communication; dollar; emerging economies; euro; exchange rate regime; reserves; Wechselkurs; Währungsreserven; Euro; US-Dollar; Yen; Schwellenländer; Internationales Währungssystem; China; OPEC-Staaten; Schwellenländer